دور السلم في إدارة المخاطر المصرفية الإسلامية : دراسة فقهية تطبيقية على بعض المصارف الإسلامية المختارة في ماليزيا - علي، موسى محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research attempts to explore how salam can be used in Islamic Banking risks Management. Therefore, the Preparatory chapter includes the overall objectives and proposed research framework. The second chapter begins with the definition of Salam and its legitimacy in Islamic law, with some of its conditions, rules, types and practical procedures for Salam contract in Islamic banks. The third chapter deals with the risk involved in terms of its concept and types, focusing on those that are directly related to this topic only, namely, financial risks. This chapter also deals with the use of financial derivatives and the opinions of jurists and contemporary scholars in its ruling, evidence and proofs. However, chapter four includes the use of Salam in managing risks, as well as patterns of applications of Salam in some Islamic banks in Malaysia. This is based on the information gathered from the questionnaire that was distributed to those banks. The researcher followed the inductive method in browsing the books and gathering the scientific material that are related to the research topic. He also followed the analytical method to analyze and discuss the views of the scholars in the issues that required so, and then the survey method by distributing questionnaire to some Islamic banks in Malaysia regarding the use of Salam in risk management. The research concluded with a number of results. The most important is that: Salam is a legitimate tool that can be used to manage risks rather than financial derivatives that are full of prohibitions. The risks that can be managed by Salam are: commodity price risk and exchange rate risk. The interviews show that Salam contracts are not used effectively in most Islamic banks in Malaysia.